Role of Purine-Rich Regions in Mason-Pfizer Monkey Virus (MPMV) Genomic RNA Packaging and Propagation - Ali, Lizna Mohamed; Pitchai, Fathima Nuzra Nagoor; Vivet-Boudou, Valérie; Chameettachal, Akhil; Jabeen, Ayesha; Pillai, Vineeta N.; Mustafa, Farah; Marquet, Roland; Rizvi, Tahir A. (Frontiers in Microbiology, 2020)
A distinguishing feature of the Mason-Pfizer monkey virus (MPMV) packaging signal RNA secondary structure is a single-stranded purine-rich sequence (ssPurines) in close vicinity to a palindromic stem loop (Pal SL) that functions as MPMV dimerization initiation site (DIS). However, unlike other retroviruses, MPMV contains a partially base-paired repeat sequence of ssPurines (bpPurines) in the adjacent region. Both purine-rich sequences have earlier been proposed to act as potentially redundant Gag binding sites to initiate the process of MPMV genomic RNA (gRNA) packaging. The objective of this study was to investigate the biological significance of ssPurines and bpPurines in MPMV gRNA packaging by systematic mutational and biochemical probing analyses. Deletion of either ssPurines or bpPurines individually had no significant effect on MPMV gRNA packaging, but it was severely compromised when both sequences were deleted simultaneously. Selective 2' hydroxyl acylation analyzed by primer extension (SHAPE) analysis of the mutant RNAs revealed only mild effects on structure by deletion of either ssPurines or bpPurines, while the structure was dramatically affected by the two simultaneous deletions. This suggests that ssPurines and bpPurines play a redundant role in MPMV gRNA packaging, probably as Gag binding sites to facilitate gRNA capture and encapsidation. Interestingly, deletion of bpPurines revealed an additional severe defect on RNA propagation that was independent of the presence or absence of ssPurines or the gRNA structure of the region. These findings further suggest that the bpPurines play an additional role in the early steps of MPMV replication cycle that is yet to be identified.